Insights into the metabolic profiling of Polygonati Rhizoma fermented by Lactiplantibacillus plantarum under aerobic and anaerobic conditions using a UHPLC-QE-MS/MS system - Wang, ZiLing; Lao, Jia; Kang, XingYi; Xie, ZhenNi; He, Wei; Liu, XiaoLiu; Zhong, Can; Zhang, ShuiHan; Jin, Jian (Frontiers in Nutrition, 2023)
Polygonati Rhizoma is a multi-purpose food with medicinal uses. In this study, Lactiplantibacillus plantarum was fermented with Polygonati Rhizoma extracts in a bioreactor under aerobic and anaerobic conditions with pH and DO real-time detection. Metabolic profiling was determined by UPLC-ESI-Q-Orbitrap-MS/MS equipment coupled with Q-Exactive Plus. Principal component analysis and orthogonal partial least-squares discriminant analysis were used to perform multivariate analysis. A total of 338 differential metabolites were selected, and 121 of these were identified by database matching, with 56 organic acids and derivatives as the main class (46.28%). The main metabolic pathways in the fermentation process are ABC transport and amino acid biosynthesis. Most of the compounds such as L-arginine, L-aspartic acid, leucine, L-lysine, citrate, inosine, carnitine, betaine, and thiamine were significantly increased during fermentation, playing a role in enhancing food flavor. Compared with anaerobic fermentation, aerobic conditions led to a significant rise in the levels of some compounds such as valine, isoleucine, and glutamate; this increase was mainly related to branched-chain amino acid transaminase, isocitrate dehydrogenase, and glutamate dehydrogenase. This study is the first report on the fermentation of Polygonati Rhizoma by L. plantarum and provides insights that would be applicable in the development of Polygonati Rhizoma fermented products.